An investigation into the effects of climate change on baleen whale distribution in the British Isles. (February 2023) - Snell, Maria; Baillie, Andrew; Berrow, Simon; Deaville, Robert; Penrose, Rod; Perkins, Matthew; Williams, Ruth; Simmonds, Mark P
Abstract: Climate change is predicted to impact the distribution of many marine species. In the North-East Atlantic and elsewhere in the world, studies indicate that climate change is leading to poleward shifts in cetacean distribution. Here, strandings data collected in the British Isles from 1990 to 2020 were used to assess whether there is evidence of a shift in baleen whale distribution. Linear regression models were used to compare the number of strandings over time between six regions of the British Isles and, whilst the results indicate no significant change in the number of strandings in the most southerly region of the British Isles, there have been significant increases in more northern regions. Data related to stranded minke whales is the primary driver of these increases, with a number of potential variables affecting this trend, including observer effort. These variables are discussed and further research to explore this potential association is suggested. Highlights: Climate change is predicted to impact the distribution of marine species. Strandings data are used to assess baleen whale distribution in the British Isles. The number of strandings from 1990 to 2020 was compared between six regions. In the most southerly region, the number of strandings remained constant. In more northern regions, the number of strandings increased significantly. Population growth and/or a northern distribution shift may explain this.